Factors of importance when selecting sows as embryo donors. (21st February 2017) - Nohalez, A.; Martinez, C. A.; Reixach, J.; Diaz, M.; Vila, J.; Colina, I.; Parrilla, I.; Vazquez, J. L.; Roca, J.; Gil, M. A.; Rodriguez-Martinez, H.; Martinez, E. A.; et al.
Abstract : The improvement in porcine embryo preservation and non-surgical embryo transfer (ET) procedures achieved in recent years represents essential progress for the practical use of ET in the pig industry. This study aimed to evaluate the effects of parity, weaning-to-estrus interval (WEI) and season on reproductive and embryonic parameters at day 6 after insemination of donor sows superovulated after weaning. The selection of donor sows was based on their reproductive history, body condition and parity. The effects of parity at weaning (2 to 3, 4 to 5 or 6 to 7 litters), season (fall, winter and spring), and WEI (estrus within 3 to 4 days), and their interactions on the number of corpus luteum, cysts in sows with cysts, number and quality of viable and transferable embryos, embryo developmental stage and recovery and fertilization rates were evaluated using linear mixed effects models. The analyses showed a lack of significant effects of parity, season, WEI or their interactions on any of the reproductive and embryonic parameters examined. In conclusion, these results demonstrate that fertilization rates and numbers of viable and transferable embryos collected at day 6 of the cycle from superovulated donor sows are not affected by their parity, regardless of the time of the year (from fall to spring) and WEI (3 or 4 days).